2021
DOI: 10.1088/1674-4926/42/12/120401
|View full text |Cite
|
Sign up to set email alerts
|

Berezinskii-Kosterlitz-Thouless phase transition in a 2D-XY ferromagnetic monolayer

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…11] 43. Meanwhile, the T BKT is also consistent with aforementioned rough estimation of T BKT based on the model of enormalization-group 46. Thus, the estimation of T BKT is reliable.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…11] 43. Meanwhile, the T BKT is also consistent with aforementioned rough estimation of T BKT based on the model of enormalization-group 46. Thus, the estimation of T BKT is reliable.…”
supporting
confidence: 72%
“…43 Meanwhile, the T BKT is also consistent with aforementioned rough estimation of T BKT based on the model of enormalization-group. 46 Thus, the estimation of T BKT is reliable. The electronic and magnetic properties of monolayer V 2 PAs are similar to that of monolayer V 2 PN, except that the former has a larger SOC effect and MAE.…”
Section: Resultsmentioning
confidence: 98%
“…54 Meanwhile, the T BKT is also consistent with the aforementioned rough estimation of T BKT by the renormalization-group calculations (see eqn (8)). 8 Thus, the estimation of T BKT is reliable.…”
Section: Resultsmentioning
confidence: 98%
“…7 The material realization of 2D-XY ferromagnets with a high transition temperature (T BKT ) is a fast-developing field and remains a challenge. 8 2D-XY ferromagnetism has been investigated in 2D hexagonal systems. In the experiment, Tokmachev et al observed that a sub-monolayer of Eu atoms self-assembled on surfaces of silicon, 9 graphene, 10 silicene, 11 and germanene 12 exhibits an easy magnetization plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation